2021
DOI: 10.3389/fonc.2021.760971
|View full text |Cite
|
Sign up to set email alerts
|

IL-6/STAT3 Is a Promising Therapeutic Target for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common malignant tumor of which the occurrence and development, the tumorigenicity of HCC is involving in multistep and multifactor interactions. Interleukin-6 (IL-6), a multifunctional inflammatory cytokine, has increased expression in HCC patients and is closely related to the occurrence of HCC and prognosis. IL-6 plays a role by binding to the IL-6 receptor (IL-6R) and then triggering the Janus kinase (JAK) associated with the receptor, stimulating phosphorylation and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 117 publications
1
72
0
Order By: Relevance
“…[ 45 ]. The signaling pathway is a significant contributor to liver cancer development and targeting the JAK/STAT3 signaling pathway is proposed as a promising therapy for HCC [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ]. The signaling pathway is a significant contributor to liver cancer development and targeting the JAK/STAT3 signaling pathway is proposed as a promising therapy for HCC [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the results obtained in the combination experiments that showed a potentiation of sorafenib cytotoxicity by caryophyllane sesquiterpenes, especially βcaryophyllene oxide, and the recognized involvement of ABC-transporters and STAT3 signaling in the progression and chemoresistance of hepato-biliary-pancreatic cancers [27][28][29][30][31][32][33], a possible modulation by treatments of this cascade in Bx-PC3, associated with the observed changes in MDR1 and MRPs pumps, was also evaluated (Figure 11). Activation of STAT3 by phosphorylation at tyrosine 705 (phospho(Tyr705)-STAT3), which is known to play an important role in the control of cell survival, proliferation, and apoptosis [34], has been measured.…”
Section: Modulation Of Stat3 Activation and Cell Migration In Sorafen...mentioning
confidence: 99%
“…It has been demonstrated that IL-6 initiates transcription of various downstream genes involved in liver development and metabolism. IL-6 can activate STAT3, promote proliferation, angiogenesis and anti-apoptotic genes, and inhibit pro-apoptotic genes, thus facilitating the proliferation and migration of HepG2 cells both in vivo and in vitro [99] , [100] , [101] ( Fig. 5 ).…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 99%
“…5 ). While ATF3-mediated up-regulation of IL-6RÎą promotes the drug resistance to sorafenib and regofinib in HCC, targeting IL-6R could increase the therapeutic efficacy of sorafenib/regofinib in advanced HCC [100] , [102] . IL-6 can upregulate the inhibitor of differentiation 1 (Id1) from bone marrow-derived myeloid cells, which is contributed to shifting dendritic cell differentiation toward myeloid-derived suppressor cells [103] .…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 99%
See 1 more Smart Citation